Geology and soil erosion assessment of Kg. Biak, Dabong, Kuala Krai, Kelantan using remote sensing and gis techniques - Zulaika Farhani Salehudin (2017)
Geological research include lithology, stratigraphy, geological structure, geomorphology and petrography in Kampung Biak, Dabong, Kuala Krai, Kelantan is located at the latitude of 5°23’30’’N to 5°25’15’’N and longitude of 101°57’30’’E to 101°59’0’’E. The objectives of this research are to prepare a slope map of the area that trigger to soil erosion at large scale using high-resolution satellite data and investigate the incidence of soil erosion features based on field survey data and satellite images. A slope map was prepared through on digitization in ArcGIS 10.0 software. Remotely sensed of Shuttle Radar Topography Mission (SRTM) 1 Arc-Second Global Digital Elevation is the most complete high resolution digital topographic database of Earth in order to identify the terrain characteristics in the study area. Three types of soil erosion features such as gully erosion, streambank erosion and sheet erosion were identified based on field survey data and satellite images.